Intermittent Rainfed Rice var. INIA 516 LM1: A Sustainable Alternative for the Huallaga River Basin - Flores Marquez, Ricardo (2025)
Climate change is projected to increase global temperatures and alter rainfall patterns. In Peru, these changes could adversely affect the central basin of the Huallaga River by increasing pest and disease incidence, evapotranspiration, and water consumption. This basin is one of the country’s main rice-producing regions, where the crop is traditionally cultivated using inefficient practices, such as continuous flood irrigation. This study evaluated the effects of different irrigation management strategies on the growth and yield of rice (Oryza sativa var. INIA 516 LM1-La Union 23), the water footprint as an indicator of water use efficiency, and the incidence of pests and diseases associated with irrigation regimes. Three irrigation treatments were implemented: Traditional flooding T1 (maintenance of a 0.15 m water layer with replenishment every 4 days), Optimized flooding T2 (replenishment every 7 days), and Intermittent rainfed irrigation T3 (replenishment every 14 days). Although no significant differences were observed in biometric parameters, yield, or pest and disease incidence, a trend of decreasing yield with longer irrigation intervals was noted: traditional flooding (7.91 t・ha−1) > reduced flooding (7.82 t・ha−1) > intermittent rainfed (7.14 t・ha−1). The incidence of white leaf virus and Burkholderia glumae was highest in the intermittent rainfed treatment, followed by optimized flooding, with the lowest incidence in traditional flooding. Yield reduction and the use of rainwater to cover water requirements resulted in a lower total water footprint for traditional flooding (834.0 m3・t−1), followed by optimized flooding (843.6 m3・t−1) and intermittent rainfed (923.9 m3・t−1). This reflects an improvement in rainwater use efficiency. The findings suggest intermittent rainfed irrigation enhanceswater use efficiency without significantly compromising rice yield or increasing disease incidence in rice var. INIA 516 LM1-La Union 23 in the central basin of the Huallaga River.